???????? ????? ??????? ?? ????? ?????? (????? ?????? ????? ?????? ?????????) - Rikhlah Ilmiyah (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2018)
Test is considered as something important in teaching-learning process for its use to limit teaching-learning process through its result. Basically, test is designed as an instrument which is useful to support learning process and to motivate students gaining a significant progress. In addition, test can be used as an instrument to evaluate students’ performance in learning a language. In some condition, a high correlation between language learning and language test may be lost. Speaking skill is known as one of language skill giving more attention on communicative competence. However, in fact, it is found that what is said by the speaker cannot be understood but by using sign language or other communication tools which is not discovered as language. Language test is useful to know students’ ability to communicate, and a discussion on language test especially speaking will be discussed in this writing. Since interview giving more highlight on the fluency and accuracy of speech, also the appropriateness of delivering ideas, it is chosen, in this research, to measure students’ oral language performance